The social functions of babbling: acoustic and contextual characteristics that facilitate maternal responsiveness. Issue 5 (17th December 2017) - Albert, Rachel R.; Schwade, Jennifer A.; Goldstein, Michael H.
Abstract: What is the social function of babbling? An important function of prelinguistic vocalizing may be to elicit parental behavior in ways that facilitate the infant's own learning about speech and language. Infants use parental feedback to their babbling to learn new vocal forms, but the microstructure of parental responses to babbling has not been studied. To enable precise manipulation of the proximal infant cues that may influence maternal behavior, we used a playback paradigm to assess mothers' responsiveness to prerecorded audiovisual clips of unfamiliar infants' noncry prelinguistic vocalizations and actions. Acoustic characteristics and directedness of vocalizations were manipulated to test their efficacy in structuring social interactions. We also compared maternal responsiveness in the playback paradigm and in free play with their own infants. Maternal patterns of reactions to babbling were stable across both tasks. In the playback task, we found specific vocal cues, such as the degree of resonance and the transition timing of consonant‐vowel syllables, predicted contingent maternal responding. Vocalizations directed at objects also facilitated increased responsiveness. The responses mothers exhibited, such as sensitive speech and vocal imitation, are known to facilitate vocal learning and development. Infants, by influencing the behavior of their caregivers with their babbling, create social interactions that facilitate their own communicative development. Abstract : Mothers responded to prerecorded examples of prelinguistic infant vocalizations that varied in vocal maturity and context. More advanced vocalizations (e.g. mature vowels) and object‐directed vocalizations were more likely to obtain a response, while vocalization directedness also influenced the type of response mothers provided (as shown here). By varying the form and context of their vocalizations, infants influence maternal behavior and may create social interactions that facilitate learning.